Penyakit Antraknosa (Colletotrichum spp.) pada Tanaman Cabai di Kabupaten Ogan Ilir - Harman Hamidson; Suwandi Suwandi; Effendy. TA (Seminar Nasional Lahan Suboptimal, 2018)
Hamidson et al, 2019. Anthracnose Disease (Colletotrichum spp.) of Chilli (Capsicum annum L) in Ogan Ilir District. pp. 129-137.Anthracnose disease is one of the obstacles in the production of red chili in the field, and is ranked first among fungal diseases. This study aims to determine the procedures and habits of farmers in cultivating red chilli plants in the field, namely the layout of the mounds and evaluation of the use of fungicides. Plant samples were taken randomly for each plot of 80 plants the plants were every harvesting  six times for 3. The percentage of disease incidence, disease severity and the extent of the curvature of the anthracnose disease (incidence and severity of the disease) showed a significant difference in the order of the mound plot. The results of evaluating the use of fungicides in vitro showed a significant difference in growth inhibitors of Colletotrichum spp.